Three dimensional echocardiography in valvular heart disease - Lee, Justin M.S.; Rana, Bushra S. (SA Heart Journal, 2017)
Although cardiac structures exist in three dimensions, two dimensional (2-D) echocardiography only provides information in a single tomographic plane, the orientation of which is determined by the ultrasound window. Accordingly the use of geometric assumptions and/or mental integration of information from multiple 2-D images are needed to assess cardiac function and structure. Advances in ultrasound technology and image reconstruction have opened up the possibility of using three dimensional (3-D) techniques in both quantitative applications such as measurement of ventricular volumes and qualitative applications such as the assessment of valve stenosis or regurgitation. Further technical improvements in terms of real-time 3-D imaging and development of 3-D transoesophageal echo (TOE ) probes; have opened up further applications including intra-operative guidance of percutaneous valve interventions.